Ατομιστικές προσομοιώσεις δισκόμορφων υγρών κρυστάλλων νανογραφενίου - Κωνσταντινόπουλος, Στέφανος (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Χημικών Μηχανικών. Τομέας Επιστήμης και Τεχνικής των Υλικών (ΙΙΙ). Εργαστήριο Επιστήμης και Τεχνικής των Υλικών, 2015)
Discotic polyaromatic molecules, similar to nanometric graphene flakes, constitute an interesting class of materials for organic electronic applications such as LEDs, FETs and solar cells. Superphenalene (C96H24) is a discotic triangular molecule consisting of 96 carbon atoms, having the ability to accept around its periphery a variety of side chains. In this thesis, molecular crystals comprised of superphenalene molecules grafted with six dodecane (C12H25) side chains are examined by means of Molecular Dynamics (MD) simulations. Structural, dynamical and mechanical properties are examined by analyzing MD trajectories generated using the LAMMPS MD simulation software. State-of-theart integration algorithms and temperature and pressure control techniques have been utilized, alongside with sophisticated mesh-based techniques for handling long range interactions. As far as the potential energy surface of the systems is concerned, well validated force fields have been employed, which reproduce physical properties in good agreement with experimental findings. A series of initial configurations corresponding to various molecular symmetries have been created and equilibrated and specific rejection protocols have been applied in order to choose the most realistic initial configuration for further studies. One major issue concerning MD simulations is whether the system under study has reached thermodynamic equilibrium or not. Two complementary methods that examine if the system has equilibrated are used: the statistical inefficiency method according to Allen and Tildesley and the autocorrelation method according to Straatsma, Berendsen and Stam. Complete structural characterizations have been carried out for all systems, focusing on the calculation of theoretical X-Ray Diffraction spectra which can be directly compared to available experimental data. Mechanical properties are also investigated, focusing on the elastic moduli of the materials computed via the volume fluctuation theory at equilibrium. Finally, the thermal motion of the molecular cores and the side chains is examined by means of dynamical studies and the manifestation of liquid crystalline behavior is probed via molecular mean square displacement calculations